1234 Emergency Urology Procedures During COVID-19 Pandemic: A 2 Monthly Prospective Study. (12th October 2021) - Georgiou, M; Ridzuan-Allen, A; Chamsin, A; Tolofari, S; Ejikeme, C; Jones, R; Siddiqui, Z; Napier-Hemy, T; Rotas, S; Hughes, K E; Khattak, A Q; McCabe, J E; et al.
Abstract: Introduction: COVID-19 resulted in Regional tiered restrictions being introduced across the UK with subsequent implications for planned and emergency care. Specific to Merseyside Tier 4 and Tier 2 restrictions were introduced in late 2020. At the onset of the pandemic in the Spring, elective work ceased, and emergency admissions were minimal. The purpose of this study was to examine the volume and nature of all emergency admissions to a Urology unit in Merseyside in the 2 nd wave of the pandemic during two different tiers of national restrictions. Method: A prospective audit examining all emergency urological activity was conducted in Whiston Hospital from October 2020 when the Tier 4 restrictions were introduced to Tier 2 was introduced. Data was obtained by identifying patients using the electronic theatre listing system. Results: A total of 52 emergency cases were performed (24 in November Tier 4, 28 in December Tier 2). A total of 12 different procedures were performed. The commonest procedure performed was stent insertion (26), followed by scrotal exploration (7). One patient required transfer to a different hospital. In total 4 calls were made by general surgery and 2 by gynaecology for urological assistance in theatre. Two urology patients returned to theatre. Direct Consultant involvement occurred in 19 cases (37%). Conclusions: Unlike the Spring lockdown acute urology operations presented despite regional restrictions. A total of 52 cases were performed with more occurring in Tier 2. Stent insertion was the commonest procedure with the majority of the cases performed by registrars.